2015
DOI: 10.5152/eurasianjmed.2015.104
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc, Copper, Magnesium and Selenium Levels in Children with Helicobacter Pylori Infection

Abstract: Objective: Helicobacter pylori infection can cause disease from mild to severe that may be accompanied by micronutrient deficiencies. We aimed to investigate serum zinc, copper, magnesium and selenium levels in Helicobacter pylori positive children. Materials and Methods:Thirty-four children, with chronic abdominal pain and diag-nosed to be Helicobacter pylori-positive and 20 healthy children with the same demo-graphic characteristics were included in the study. Serum zinc, copper and magnesium levels were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 16 publications
3
26
0
1
Order By: Relevance
“…in 67 H. pylori seropositive and 94 seronegative children, without finding any significant difference between groups. Two Turkish groups looked at deficiencies of other micronutrients than iron in relation to H. pylori status including reduced holotranscobalamin levels indicating vitamin B12 deficiency and levels of zinc, copper, magnesium, and selenium . However, both studies had major methodical limitations not allowing firm conclusions.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…in 67 H. pylori seropositive and 94 seronegative children, without finding any significant difference between groups. Two Turkish groups looked at deficiencies of other micronutrients than iron in relation to H. pylori status including reduced holotranscobalamin levels indicating vitamin B12 deficiency and levels of zinc, copper, magnesium, and selenium . However, both studies had major methodical limitations not allowing firm conclusions.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…29,30 Growth is an important but complicated issue; hence, the association between growth and H. pylori infection needs further study. Nurinnisa finds out that the serum concentration of zine is dramatically higher in children with H. pylori infection, but the elements of copper and magnesium have no differences between infected and noninfected children, 31 and Anla reports that there are no significant differences in contents of calcium, magnesium, iron, zinc, selenium, and copper between the two groups. 32 Besides, iron deficiency anemia is revealed to be associated with H. pylori infection.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies demonstrated that Hp infection was associated with the deficiency of copper, vitamin B 12 , folic acid, and vitamin A, C, and E [25, 26]. These deficiencies originate from the anorexia caused by dyspeptic symptoms and malabsorption secondary to intestinal bacterial infections, which is the resultant of hypo-achlorhydria in the presence of Hp [27]. Gulsen et al found a statistically significant increase in the serum B 12 and folate levels after Hp eradication [28].…”
Section: Discussionmentioning
confidence: 99%